Political trust and informal traders in African cities - Resnick, Danielle; Sivasubramanian, Bhavna (Cambridge University Press, 2023)
How do cities foster political trust among informal workers? This question is particularly salient in Africa's growing cities where local governments must reconcile policy priorities across highly heterogeneous constituencies, including a burgeoning middle-class and a large informal economy. We argue that expectations about reciprocity and procedural justice shape the probability that informal traders trust their local government. In doing so, we analyse a survey of approximately 1000 informal traders in Ghana's three main cities – Accra, Kumasi and Tamale. We find that traders who paid requisite fees to local assemblies and could attribute a benefit from those payments were more likely to trust their local government while those who had experienced harassment by city authorities were less likely to do so. The paper highlights that drivers of trust among diverse urban constituencies deserve greater empirical and comparative attention, especially as countries deepen decentralisation initiatives and cities commit to development goals around inclusivity.